2013
DOI: 10.1590/s0044-59672013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Biological and morphometric aspects and rearing of Syssphinx molina (Cramer) (Lepidoptera: Saturniidae), a defoliator of parica tree

Abstract: The objective of this research was to describe the biological and morphometric aspects of the parica tree defoliator, Syssphinx molina (Cramer), and make recommendations about the insect rearing. The life cycle was 62.9 days with mean periods for the egg, larval, pre-pupal and pupal stages of 5.6, 31.1, 2.2 and 16.6 days respectively. The pupal viability was 60.5% for females and 48.6% for males. The sexual ratio was 0.5 with mean production of 182.3 ± 2.2 eggs per female and egg viability of 24.3%. The mean l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…Currently, the greatest obstacles to increase paricá productivity are the biotechnological (cloning and genetic breeding) and phytosanitary aspects, which still require applied research, since expansion of parica planted areas was not followed by phytosanitary actions, such as systematic monitoring of insects and the understanding of damages due to wood-degrading organisms (Tremacoldi et al, 2009) and insects, like Pantophthalmus kerteszianus and P. chuni (Lunz et al, 2010b) or Syssphinx molina (Batista et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the greatest obstacles to increase paricá productivity are the biotechnological (cloning and genetic breeding) and phytosanitary aspects, which still require applied research, since expansion of parica planted areas was not followed by phytosanitary actions, such as systematic monitoring of insects and the understanding of damages due to wood-degrading organisms (Tremacoldi et al, 2009) and insects, like Pantophthalmus kerteszianus and P. chuni (Lunz et al, 2010b) or Syssphinx molina (Batista et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Brazilian Association of Forest Plantation Producers -Abraf (2010), the parica tree wood is used in the manufacturing of plywood, laminates, medium density fiberboard (MDF), ceilings, toothpicks, paper, furniture, interior finishing and moldings. Some studies identified the aerial insect fauna associated with the parica tree (Lunz et al, 2011;Batista et al, 2013), but there are no reports of the edaphic insect fauna in the specialized literature. It is known that forest ecosystems accumulate a layer of organic residues on the soil.…”
Section: Introductionmentioning
confidence: 99%
“…O número de espécies e gêneros diminui com o aumento da latitude; não havendo registro para os extremos norte e sul (LEMAIRE; MINET, 1998 (CÂMARA et al, 2011). A espécie possui um conjunto de características que despertam o interesse fitossanitário, pois tem altíssimo potencial de praga agrícola: a fêmea adulta deposita 102.5 ± 2.3 ovos por dia, chegando até 290 ovos por fêmea; a larvas pode consumir toda a folhagem da planta alimento (BATISTA et al, 2013). A larva é polifágica, ou seja, se alimenta da folhagem de diversas plantas, tais como Ficus retusa L. (Moraceae) e as espécies de acacia, cassia, inga e parica (Fabaceae) (SILVA et al, 1968).…”
Section: Além Da Importância Agrícola As Larvas Dos Gêneros Automerisunclassified